CHARACTERISTICS OF CHILDREN INFECTED WITH MALARIA AT BLU NABIRE DISTRICT HOSPITAL YEAR 2023 - popang, Chrsitin popang (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
Malaria that occurs in children can pose a major risk to their growth and development. One in four Indonesians lives in an area with a high risk of contracting malaria. In 2016 malaria killed 161 people in Indonesia. Globally this disease killed 445,000 people in the same year. Research Objectives were to determine the characteristics of children infected with malaria. This type of research uses research techniques with a quantitative descriptive method. The population in this study were parents of children infected with malaria who were hospitalized or outpatient for 6 months from January – July 2023 at the BLUD of Nabire Regency Hospital, totaling 57 children, and the sample used was total sampling. It was found that the highest number of children infected with malaria was 0-5 years old with a percentage (64.9%), the highest number of children's gender was male (57.9%), the type of malaria that infects children was tertian malaria with a percentage of (57.9%), the highest initial complaint when children are hospitalized is moderate, namely (70.2%), and the environment where children infected with malaria live is coastal/beach areas (50.9%) and nearby houses. with forests/bushes (64.9%) and the habit of not using mosquito nets when sleeping (64.9%).